Lógicas institucionais e inovação grassroot: um estudo em negócios veganos - Zanin, Luis Miguel (2020)
This work aims to contribute by better understanding how institutional logics, through the hybridization of institutional logics, influence the creation and acceptance of innovations in the context of grassroot innovations. Thus, it contributes to the field of innovation too, understanding how innovation happens in a context of pressure from social movements, in addition to environmental pressures, where the success of an innovation is not only measured by the result for organizations, but for society as well. To achieve this goal, this thesis is divided into two studies. The first is an analysis of bibliographic coupling to identify study opportunities in institutional logic, institutional complexity and hybridization of logic. The second is an empirical study that sought to identify how, and which logics were hybridized and how this contributed to the emergence of grassroot innovations and how it contributed to their acceptance and dissemination. For that, 52,423 posts from 35 Brazilian vegan brands active in the fashion, cosmetics, supplements and fairs segments were analyzed. The results indicate that the logics belonging to the institutional orders of community, market and profession were hybridized and that, because there are several logics, not all of them act in the purchase of vegan products and that, despite these quantities, these logics result in divergent behaviors or conflicts in the field.